Relationship Of Mom's Knowledge About Delivery Technique And Perineum Rupture In Normal Delivery At The Yani Delitua Midwife Clinic In 2022 - Rini Febrianti (Pena Cendekia Insani, 2022)
Normal delivery is the process of expelling the products of conception that have been enough months, born spontaneously with a back of the head presentation that takes place within 18 hours, without complications to both the mother and the fetus. Pregnant women are really looking forward to the arrival of the time of delivery, because they crave the presence of the baby who has been waiting for 40 weeks. The formulation of the problem in this study is